Assessment of the Safety of Chronic Administration of Selenium Enriched Yeast - Hanaa H. Ahmed, EL-S M.E. Mahdy, Hatem A. EL-mezayen, Rehab M. Hussien (Journal of Applied Pharmaceutical Science, 2013)
This study aimed to achieve a balance between selenium (Se) incorporation and optimal growth of yeast (Saccharomyces cerevisiae) cells, and to assess the safety of administration of selenium-enriched yeast (Se-Y) in comparison with inorganic sodium selenite in experimental animals. Se as sodium selenite was incorporated into yeast cells in different concentrations (19, 39 and 57 µM Se), then dry yeast biomass, yeast cell viability and Se content of the yeast were evaluated. Acute toxicity of Se, yeast (Saccharomyces cerevisiae) and Se-Y were determined. In chronic toxicity study, one hundred and eight (male and female) rats were classified into 10 groups. Group (1) was control. Groups 2, 3 and were given three dose levels of Se 3.8, 1.91 and 0.95 mg/kg/day respectively for 3 months. Groups 5, 6 and 7 were given three dose levels of yeast 250, 125 and 66.5 mg/kg/day respectively for 3 months. Groups 8, 9 and 10 were given three dose levels of Se-Y 250, 125 and 66.5 mg/kg/day respectively for 3 months. Heamoglobin (Hb) concentration, white blood cells (WBCs) count, serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) activity, urea and creatinin levels were determined. Moreover, histopathological examination of liver and kidney tissue sections were evaluated. With the increase of Se concentration added to the fermentation medium, the significant increase in the selenium content in yeast cells was recorded. While, the increased Se incorporation in the yeast caused a significant decrease in dry yeast biomass and cell viability as compared to blank. The present results also showed that animals administered yeast at different doses for 3 months displayed nearly no changes in the studied biochemical parameters. Administration of Se or Se-Y in high and intermediate doses significantly decreased Hb level and WBCs counts, while they caused significant increase in ALT, AST, ALP activity as well as urea and creatinin levels. Administration of Se or Se-Y in low dose exhibited nearly no changes in AST activity while they caused significant increase in ALT and ALP activities. Moreover, administration of Se in low dose caused significant increase in urea and creatinin levels in both male and female rats. These results are well documented by histopathological findings. The present study indicated that 19 µM Se could be the proper concentration for achieving the optimal growth of yeast cells. Additionally, this study asserted the safety of chronic administration of Se-Y compared with inorganic Se.
Keywords: Selenium, Saccharomyces cerevisiae, Seleinum -enrich